OP67 Activity levels in mothers and children during the transition to primary school: findings from the southampton women's survey. (2nd September 2017) - Hesketh, KR; Brage, S; Ekelund, U; Cooper, C; Godfrey, K; Harvey, NC; Inskip, H; Robinson, S; Sluijs, EM van
Abstract : Background: Parental physical activity (PA) is frequently investigated as a potential correlate of preschool-aged children's PA, yet there is little information about how the association between parent-child PA changes during the transition to formal schooling. We aimed to determine the association between objectively measured maternal and 6-year-old children's PA, exploring how this association differs by demographic and temporal factors; and 2) identify how this association changes during the transition to school (from 4–6 years). Methods: Data were from the UK Southampton Women's Survey. PA levels of 530 6-year-olds and their mothers were measured concurrently using accelerometry for up to 7 days. Two-level mixed-effects linear regression was used to model the association between maternal-child PA at age 6 [average activity intensity (ACC); minutes spent sedentary (SED); and in moderate and vigorous PA (MVPA)]. Interactions with demographic and temporal factors, and how the association differed across the day (morning (6–9am); school (9am-3pm) and evening (3–11pm)), were tested. Change in the association between maternal-child PA (at age 4 and 6, n=170) was also assessed. Results: At age 6, mother-child daily PA were positively associated at all activity intensities: ACC: β=0.24 [95% CI: 0.19, 0.30] counts per minute; SED: 0.23 [0.20, 0.26] minutes/hour; MVPA: 0.53 [0.43, 0.64] minutes/hour. The association was stronger between mother-child PA at all intensities at the weekend (vs. weekdays: ACC: βinteraction =0.16 [95% CI: 0.06, 0.25] counts per minute; SED: 0.07 [0.02, 0.12] minutes; MVPA: 0.44 [0.24, 0.64] minutes). For SED, the mother-child association was stronger for children with older siblings (vs. none); for MVPA, the relationship was stronger for those who had both younger and older siblings (vs. none). Longitudinally, the mother-child association did not differ with age for SED and light PA (LPA); mother-child ACC and MVPA were significantly weaker at age 6 compared with age 4 (difference in ACC: −0.23 [-0.37, –0.10], MVPA: −0.16 [-0.31, –0.00]). This difference was driven by a weaker relationship in the mornings and during the school day (9–3pm). Discussion: Maternal-child PA levels are positively associated at age 6, with stronger associations at weekends, and in those with siblings in the home. From age 4 to 6 years, the mother-child ACC and MVPA association weakened. This may reflect decreasing co-participation with age, as children gain independence/engage in more structured PA at school. Different intervention foci may be needed before and after the transition to school, but family-based PA remains an important element of children's overall PA.